Types of exposure to the Lebanese- Israeli war of July- August 2006 in the eyes of youth, children and their parents - Abou Chedid, Kamal (Beirut Lebanese Association for Educational Sciences; Kuwait Society for the advancement of Arab, 2008)
This chapter deals with the July War related accidents and also examines other accidents related to personal acts of violence as well as other accidents that usually take place outside the scope of wars. It also aims to determine the frequency and types of accidents to which children and adolescents are exposed to in Lebanon during the war initiated by Israel against Lebanon and prior occurrences. Furthermore, it aims to identify the groups contained in the study that were at most risk for exposure to accidents based on variances in gender, religion, age, province and educational sector. As for accidents that were recorded after the July War, data was gathered based on the responses of pollsters to an open-ended question in which they were asked to recount an accident that greatly impacted them and one that took place one month prior to conducting the survey.
: Chapter in a Book
Keywords: Psychological Health; Santé psychologique; 2006